2007
DOI: 10.1111/j.1742-4658.2007.05645.x
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative lifestyle in yeasts belonging to the Saccharomyces complex

Abstract: The concentration of oxygen in the environment is one of the most important factors that regulate energy conversion in living cells. Organisms have developed multiple processes to optimize the utilization of oxygen when its availability is reduced. According to the role of oxygen in their metabolism, yeasts can be classified as: (a) obligate aerobes, displaying an exclusively respiratory metabolism; (b) facultative fermentatives, displaying both respiratory and fermentative metabolism; and (c) obligate ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
211
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(225 citation statements)
references
References 52 publications
13
211
0
1
Order By: Relevance
“…The rise in temperature and ethanol as a result of the Crabtree effect trait was operated on by natural selection because it increased S. cerevisiae's fitness. It seems this is an adaptation that only S. cerevisiae possesses in this particular community: none of the other species were able to ferment the grape juice to completion (M. R. Goddard, unpublished data), and their lineages are all positioned before the yeast whole-genome duplication event and therefore demonstrate either an absence or significantly diminished Crabtree effect (Merico et al 2007). These data correlate with the reports that S. cerevisiae dominates more rapidly in traditional ferments with higher temperature (Heard and Fleet 1988), and observations that higher temperature ferments experience less problems from non-Saccharomyces yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…The rise in temperature and ethanol as a result of the Crabtree effect trait was operated on by natural selection because it increased S. cerevisiae's fitness. It seems this is an adaptation that only S. cerevisiae possesses in this particular community: none of the other species were able to ferment the grape juice to completion (M. R. Goddard, unpublished data), and their lineages are all positioned before the yeast whole-genome duplication event and therefore demonstrate either an absence or significantly diminished Crabtree effect (Merico et al 2007). These data correlate with the reports that S. cerevisiae dominates more rapidly in traditional ferments with higher temperature (Heard and Fleet 1988), and observations that higher temperature ferments experience less problems from non-Saccharomyces yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, this non-Saccharomyces yeast is classified among the Crabtree-negative 18) or Crabtree-positive organisms, but with less sensitivity than Saccharomyces according to Alves-Araujo et al 12) and Merico et al 17) These authors explain that even under limited oxygen conditions, the yield of biomass production of T. delbrueckii remains higher than that of S. cerevisiae due to the greater proportion of carbon that can flow in the respiratory metabolism. Our results are in accord with these last authors.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it has been reported that T. delbrueckii does not grow under anaerobic conditions. [14][15][16] In a variety of studies, it is also classified as a Crabtree-positive 12,17) or a Crabtreenegative species. 18) The objective of this study was to test and quantify the influence of oxygenation on the metabolism of one T. delbrueckii strain selected for wine production.…”
mentioning
confidence: 99%
“…Plotted points in panel c show the rate and yield of glucose metabolism in exponentially growing cultures of yeast species. Data are taken from Merico et al (2007). Species that ferment glucose to produce ethanol are shown with open symbols and those species that do not produce ethanol are shown with filled symbols.…”
Section: Metabolic Constraints Generate Social Conflictsmentioning
confidence: 99%